Efetividade do tratamento clínico em mulheres com diagnóstico de endometriose e dor pélvica crônica - Mello, Thais Farias Koch [UNIFESP] (2021)
Introduction: Endometriosis is a chronic disease that preferentially affects young women and at reproductive age, whose delay in diagnosis and, consequently, in treatment, can significantly affect patients' quality of life. Clinical treatment of symptoms related to endometriosis is a valid option as a first line of therapeutic approach, with good results on pain symptoms relief and as an alternative for when the surgical approach is not possible immediately. Objective: To evaluate the effectiveness of clinical treatment in relieving the symptoms of with chronic pelvic pain and endometriosis. Methods: Retrospective study with review of the medical records of patients with clinical and radiological diagnosis of endometriosis, with symptoms for more than six months and followed up at the Pelvic Pain and Endometriosis outpatient clinic (UNIFESP), with care beginning between January 2010 and December 2012. Patients were divided according to the classification of endometriosis by imaging exams; aspects of the clinical treatment used (type of drug treatment, number of medications, length of follow-up) were evaluated in relation to its effectiveness (improvement in the symptoms reported by the patients). Data on the care and follow-up of these patients were extracted until 12/31/2016. Results: Among the 316 patients seen during the study period, 169 were considered eligible. Significant improvement of symptoms was observed in 69,8% of women who underwent through clinical treatment, of which 87% used hormonal medication and 13% non-hormonal medication. Conclusion: Our study demonstrated that clinical treatment in patients with endometriosis, for a maximum period of six years of follow-up, is effective, with improvement in the symptoms reported by the patients and with rates similar to those described in the literature.